Binocular visual performance and optical quality of trifocal intraocular lens in Chinese patients with high myopic cataract - Baoxian Zhuo; Wenqian Shen; Lei Cai; Shuang Ni; Limei Zhang; Xu Chen; Haike Guo; Jiying Shen; Jin Yang (PLoS ONE, 2025)
Purpose To evaluate the visual performance and optical quality of a trifocal intraocular lens (IOL) in patients with high myopic cataracts. Methods This is a prospective, multicenter, non-randomized cohort study. Patients scheduled for cataract surgery with binocular AcrySof IQ® PanOptix® TFNT00 IOL implantation were enrolled. Participants with axial length (AL) ≥ 26 mm were assigned to the high myopia group, while age- and sex-matched patients with AL < 26 mm in the control group. Key outcomes measured included uncorrected distance visual acuity (UDVA), intermediate and near visual acuity (UIVA, UNVA), best-corrected distance visual acuity, defocus curve, contrast sensitivity, visual quality (objective and subjective), and reading ability. Results 58 eyes from 29 patients in the high myopia group and 56 eyes from 28 patients in the control group were included. Both groups showed significant improvements in visual acuity postoperatively although the UIVA and UNVA of patients with high myopia were significantly worse than those in the control group after 1 month, 3 months, and 1 year (both P < .05). The high myopia group had lower mean visual function-index scores for near-range activities and fewer photic phenomena (halo) than the control group (all P < .05). Preferred reading distance and speed did not differ significantly between the groups. Conclusions Trifocal IOL implantation improved visual acuity in both groups. However, patients with high myopia experienced significantly poorer intermediate/near vision outcomes and also less complains about photic phenomena than controls. These findings support cautious patient selection and preoperative counseling for this population.